Labour market effects of the 2006 Soccer World Cup in Germany - Florian Hagn; Wolfgang Maennig (University of Hamburg, Faculty of Business, Economics and Social Sciences, Chair for Economic Policy, 2007)
This study analyses for the first time on the basis of a multivariate analysis ex post the effects on the jobs market of a soccer World Cup, in this case the 2006 World Cup held in Germany. In addition to three methods already used for other analyses in studies of sporting events, an extended Difference-in-Difference estimate is used in order to compare the development of the numbers of unemployed in the 12 World Cup venues with the development of the numbers of unemployed in 62 other German cities. The results demonstrate that in none of the respective match venues did the effect of the sporting event on unemployment differ significantly from zero.
Keywords: L83; R53; R58; 330; Labour market; regional economics; sports economics; World Cup; Stadium Impact